Direct competition preparation in elite high jumping - Bora, P. (New Studies in Athletics, 2012)
A time to focus on peaking for the main competition of the year, for example the European Championship, World Championships or Olympic Games, is a key element of current training theory and is known as Direct Competition Preparation. Proper training in this period can have a positive impact on the results achieved. However, improper, e.g. excessive, training may lead to disappointing results. It is therefore very important for the coach to plan appropriate training loads and select appropriate drills and other training content in this period. Moreover, the programme should be individualised for the athlete and conditioned on the demands of the competition schedule and the extent to which the annual training plan has been implemented. The author, who is a national coach for the jumping events in Poland, outlines the principles for planning the Direct Competition Preparation and provides typical workouts for elite high jumpers based on relevant literature and his personal experience.